Wear of Ceramic Tools When Machining Nodular Cats Iron - L.A Husni; C Choudhory; A.K Ghani (ASEAN Journal on Science and Technology for Development, 2000)
Wear of Ceramic Tools When Machining Nodular Cats Iron